Hybrid sunflower seed yield, composition and deterioration after chemical desiccation - Szemruch, Cyntia Lorena; Cantamutto, Miguel Angel; García, F.A.; Aguirre, M.; Renteria, S.J.; Rondanini, Deborah Paola (2018)
The impact of chemical desiccation on yield showed contrasting results depending on seed moisture content at the time of application. Its effects on seed deterioration are still unknown and could be modified by seed composition. Objectives were to evaluate the impact of chemical desiccation on: i) hybrid sunflower seed yield and composition at harvest time, ii) seed deterioration during long-term storage and iii) the relationship between seeds deterioration and oil or oleic acid content. Six hybrids including low, mid and high oleic were evaluated in three experiments. Two treatments were applied on female lines at 27-30% seed moisture: (i) spraying with Paraquat and (ii) detaching heads with a knife. Control remained in the field until 10% seed moisture. Seeds were stored during 19 months under room and cold chamber conditions. Yield, number of seeds and hybrid seed composition (thousand seed weight, kernel percentage, oil and acid oleic content) were determined. Seed deterioration during storage was analyzed by germination and vigour. Paraquat advanced harvest by 35-43 days, without affecting yield or seed composition. During storage the germination of Paraquat treatments remained above that of control, without differences between storage conditions, while vigour remained above control only in cold chamber, for low oleic hybrids. Associations between deterioration (germination and vigour) and oil or oleic acid content, were not significant. Desiccation with Paraquat allows advanced harvest without yield losses or modifications in seed composition. The deterioration of desiccated seeds was lower and independent from oil and oleic acid content.